Analysis Sector Potential And Contribution of Agriculture In Increasing Gross Regional Domestic Product (GRDP) of Banyumas Regency - Rahmat Hidayatullah; Watemin Watemin; Yusuf Enril Fathurrohman (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aimed to analyze the potential and contribution of the agricultural sector to the Gross Regional Domestic Product (GRDP) of the Banyumas Regency. Methodology: This study employed documentation techniques to acquire secondary data from various official sources, utilizing secondary data analysis techniques. Results: The agricultural sector was evaluated using Location Quotient (LQ) and Dynamic Location Quotient (DLQ) analyses, while the potential of leading commodities was visualized using a geographic information system (GIS). Findings: The results showed that the agricultural sector in Banyumas Regency plays a significant role in the regional economy, although it is a non-base sector based on the LQ analysis. However, several subdistricts showed promising potential in leading commodities such as rice, corn, and coconut. Novelty: DLQ analysis indicated the future growth potential of the agricultural sector, while Klassen typology and Shift Share analysis provided an overview of the structure and dynamics of the regional economy. Originality: The results of this study are expected to serve as a reference for the local government in formulating more focused and sustainable development policies, especially in improving the competitiveness of the agricultural sector in Banyumas Regency. Conclusion: It is recommended that the Banyumas Regency government optimize leading commodities, improve rural infrastructure, expand market access, and encourage technology and innovation to maximize the potential of this sector. Type of Paper: Research article.